Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament Berbantuan Media Scrapbook diengkapi Question Card terhadap Hasil Belajar Siswa - Jawa, Intan Ana; Bano, Vidriana Oktoviana; Ndjoeroemana, Yohana (Pustaka Digital Indonesia, 2025)
The urgency of this research is the low learning outcomes of students at SMPN Satap Padammu, as evidenced by the final summative scores for the 2024/2025 semester. This issue necessitates innovative learning methods that can improve student understanding and actively engage students. This study aims to determine the effect of Team Games Tournament Type Cooperative Learning Model assisted by Scrapbook Media Equipped with Question Cards on Student Learning Outcomes at SMPN Satap Padammu. This research is a quasi - experimental research with a comparative quantitative associative. The subjects of this study were students of class VIII IPA A (as a control class) as many as 29 people and class VIII B (as an experimental class) as many as 26 people with a total of 55 people at SMPN Satap Padammu. The data collection instruments used were interviews, observations, and written tests in the form of pretests and postests. The results of this study based on hypothesis testing using the paired sample t test showed that the Asymp. Sig (2-tailed) 0.001 <0.05. Thus, it can be concluded that H0 is rejected and H1 is accepted. That is, there is a significant effect of the Team Games Tournament (TGT) learning model assisted by Scrapbook media equipped with Question Cards on student learning outcomes. This research is expected to conduct research development at different levels with other subjects in order to obtain broader and deeper results regarding the TGT (Teams Games Tournament) learning model assisted by scrapbook media equipped with Question cards.